2020
DOI: 10.1177/0269215520932964
|View full text |Cite
|
Sign up to set email alerts
|

Resistance training in stroke rehabilitation: systematic review and meta-analysis

Abstract: Objective: This systematic review and meta-analysis investigates the effects of resistance training in supporting the recovery in stroke patients. Data sources: PubMed, the Cochrane Central Register of Controlled Trials and the PEDro databases were reviewed up to 30 April 2020. Review methods: Randomized controlled trials were included, who compared: (i) resistance training with no intervention, (ii) resistance training with other interventions and (iii) different resistance training protocols in stroke rehabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 75 publications
(334 reference statements)
3
36
0
5
Order By: Relevance
“…Os principais motivos de exclusão foram: revisões sistemáticas contendo protocolos de TR misto, com outras modalidades de treinamento, que não foram realizadas análises de resultados individuais para cada modalidade, revisões sobre TR muscular inspiratório e revisões que tiveram por finalidade investigar os princípios da prescrição do TR e/ou analisar protocolos de prescrição. Por fim, dez (10) estudos [8][9][10][17][18][19][20][21][22][23] atenderam aos critérios de elegibilidade, sendo sumarizado na Figura 1.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Os principais motivos de exclusão foram: revisões sistemáticas contendo protocolos de TR misto, com outras modalidades de treinamento, que não foram realizadas análises de resultados individuais para cada modalidade, revisões sobre TR muscular inspiratório e revisões que tiveram por finalidade investigar os princípios da prescrição do TR e/ou analisar protocolos de prescrição. Por fim, dez (10) estudos [8][9][10][17][18][19][20][21][22][23] atenderam aos critérios de elegibilidade, sendo sumarizado na Figura 1.…”
Section: Resultsunclassified
“…No tocante a força muscular e ganhos em 1RM, os estudos incluídos sugerem que houve um aumento estatisticamente significativo nos indivíduos que realizaram o TR [8,[18][19][20][21][22][23]. Contudo, esses resultados podem não ser clinicamente importantes.…”
Section: Discussionunclassified
“…Weight-bearing exercise also results in the prevention of osteoporosis [10]. For a majority of people in rehabilitation or with an innate disability, such as following stroke or orthopaedic surgery, strength training for feeble muscles is a vital feature to improve recovery [14]. Several studies examined the impact of resistance training on different categories of body mass index [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis found that progressive resistance exercise at higher intensities improves strength in this population [ 5 ]. However, systematic reviews and meta-analyses paint an unclear picture of the role that strength training of the lower extremity and associated strength gains play in improving gait in persons who have experienced a stroke [ 6 8 ]. Possible factors preventing strength gains from translating into functional performance may include suboptimal training intensities and duration and/or a lack of appropriate progression of the intervention [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, small effect sizes of strength training on gait parameters in this population may be the result of a lack of specificity of muscles selected and a failure to improve multiarticular movements requiring muscle activation of a coordinated group of muscles involved in locomotion. Strengthening exercises involving multiarticular muscles (e.g., leg press) appear to be better at improving strength and function in individuals with hemiparesis than isolated monoarticular exercises such as leg extensions [ 8 ].…”
Section: Introductionmentioning
confidence: 99%